Pengaruh Budaya Toraja Ma’nene’ Terhadap Identitas Sosial Masyarakat di Dusun Malombu Kecamatan Awan Rantekarua Kabupaten Toraja Utara - Kesya Payungallo; Muh Said; Shasliani Shasliani (Universitas Negeri Gorontalo, 2026)
This study aims to find out: 1) The description of Toraja ma'nene' culture in Malombu Hamlet, Awan Rantekarua District, North Toraja Regency, 2) The description of the social identity of the community in Malombu Hamlet, Awan Rantekarua District, North Toraja Regency, and 3) The influence of Toraja ma'nene' culture on the social identity of the community in Malombu Hamlet, Awan Rantekarua District, North Toraja Regency. This study uses a quantitative approach with a type of quantitative descriptive research. The research variables consisted of ma'nene' (variable X) and social identity (variable Y). Data collection techniques use observation, questionnaires and documentation. Meanwhile, the analysis techniques used are descriptive statistical analysis and inferential statistical analysis using the help of SPSS 26. The results of the study showed that: 1) The description of Toraja ma'nene' culture in Malombu Hamlet, Awan Rantekarua District, North Toraja Regency was in the